Nepal's Attempt to Escape Asymmetrical Interdependence with India - Dahal, Gaurav Raj (Journal of Political Science, 2019)
Nepal and India share interdependence with each other regarding economy and politics. India, as a powerful nation with adequate structural power, has been seen meddling with Nepal’s internal affairs and exploiting its economic and political vulnerability. The overall objective of this paper is to analyze the Nepalese foreign policies towards India and its attempt to escape this asymmetrical interdependence throughout the history till date. This paper also tries to identify the factors that influence the formulation of Nepalese foreign policies as well as the consequences of the implemented policies. Additionally, the study shows that with the ongoing radical changes brought by series of democratic successes in Nepalese political system, the traditional approach of Nepalese political leaders that existed before can be changed. Nepal is at a critical juncture where the policies it will make can change significantly with the assistance of international and regional regimes.